2014
DOI: 10.1186/1756-0500-7-629
|View full text |Cite
|
Sign up to set email alerts
|

Causes of death among females–investigating beyond maternal causes: a community-based longitudinal study

Abstract: BackgroundIn developing countries, investigating mortality levels and causes of death among all age female population despite the childhood and maternal related deaths is important to design appropriate and tailored interventions and to improve survival of female residents.MethodsUnder Kilite-Awlealo Health and Demographic Surveillance System, we investigated mortality rates and causes of death in a cohort of female population from 1st of January 2010 to 31st of December 2012. At the baseline, 33,688 females w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Intensifying TB screening into RCH services, diabetic and other clinics would increase TB case detection and patients receiving care is hereby recommended. Literature suggests that the magnitude of TB among women attending RCH clinics is high [12] , [13] , [14] and people with diabetes are at increased risk of infections and reactivation because their immuno-compromised status [15] . Ending TB and diabetes requires a joint response to ensure that all people with TB and those with diabetes have access to much-needed care on both fronts [16] , and the WHO recommends systematic screening for TB in people with diabetes especially in settings with high TB prevalence [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Intensifying TB screening into RCH services, diabetic and other clinics would increase TB case detection and patients receiving care is hereby recommended. Literature suggests that the magnitude of TB among women attending RCH clinics is high [12] , [13] , [14] and people with diabetes are at increased risk of infections and reactivation because their immuno-compromised status [15] . Ending TB and diabetes requires a joint response to ensure that all people with TB and those with diabetes have access to much-needed care on both fronts [16] , and the WHO recommends systematic screening for TB in people with diabetes especially in settings with high TB prevalence [17] .…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous studies conducted in peaceful settings, which have consistently found that infectious diseases and pregnancy-related causes are the main killers among women in developing countries [ 24 – 27 ]. In some studies, even infectious disease related deaths alone outnumber NCDs and external causes combined [ 25 , 26 ]. Although infectious diseases were dominant even in non-conflict settings, research shows that the impact of infectious diseases usually increases after armed conflicts, mostly due to health system disruption [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The KA-HDSS is a member of the INDEPTH Network [ 16 ]. Details of the surveillance system, study population, and operating procedures have been published previously [ 2 , 17 19 ]. The surveillance started with a baseline population of 66,453 individuals living in 14,453 households.…”
Section: Methodsmentioning
confidence: 99%